TINDAK PIDANA MENERAPKAN SISTEM SKEMA PIRAMIDA DALAM PENDISTRIBUSIAN BARANG OLEH PELAKU USAHA - Julius Sitangihonon Sihotang; Kartika Pakpahan; Hilda Siregar; Yunepa Pebi Yanti Sembiring; Kevin Dwiputra Sitorus (Jurnal Darma Agung, 2020)
The sales system in the form of a pyramid scheme is prohibited in Article 9 of Law Number 7 of 2014 concerning Trade because it can harm the people who are its members. In the pyramid scheme sales system, the concept is almost close to the concept of a multi-level marketing sales system, which creates opportunities for companies by running a pyramid scheme that bills itself as an official multi-level marketing company. This study aims to analyze the positive law on the prohibition of distribution business actors in the application of the pyramid scheme system and about the efforts to overcome criminal acts by implementing a pyramid scheme system in the distribution of goods. This study analyzes the main problems with the scope and identification of the problems through the Normative Juridical Approach with descriptive analytical research. The existence of various forms of driving factors for the development of companies with a pyramid scheme sales system is the characteristic of most Indonesians who want to have large income instantly, with public awareness and law enforcement officials about the dangers of pyramid schemes that are still lacking, so that the distribution of goods with a pyramid scheme system is carried out by If business actors make mistakes or violate regulations from the government regarding pyramid scheme businesses, those who carry out such actions will be subject to sanctions either by fines or imprisonment.